High-melting-point propylene-ethylene olefin polymer elastomer and preparation method thereof
By copolymerizing propylene and ethylene under anhydrous and oxygen-free conditions, a high melting point ethylene propylene polymer elastomer is solved, and the problems of low melting point and insufficient strength of traditional propylene-based elastomers are achieved, achieving higher performance and a wider application range.
Patent Information
- Application Number
- CN202510021543.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-01
AI Technical Summary
The melting point of traditional acrylic elastomers is low, which limits their application range in high temperature environments, and is insufficient in strength, making it difficult to provide sufficient structural support and protection in scenarios where large external forces are affected.
Copolymerization of propylene and ethylene using a single active center metallocene catalyst or a postmetallocene catalyst under anhydrous and oxygen-free conditions is formed to form a high melting point ethylene propylene polymer elastomer, which improves its melting point, strength and elongation of breakage.
The melting point, strength and elongation of the acrylic-based elastomer are significantly improved, allowing it to show better performance in high temperature and high external force environments, and expand its application range.
Smart Images

Figure CN119735728A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polyolefin elastomers, in particular to a high melting point propylene ethylene polymer elastomer and a preparation method thereof. Background Art
[0002] Propylene-based elastomer is an elastomeric material polymerized with propylene as the main monomer. The molecular chain contains propylene units and has certain elasticity and flexibility. Its molecular structure usually includes a crystalline phase and an amorphous phase. The crystalline phase provides a certain strength and rigidity, while the amorphous phase gives the material elasticity. Since propylene-based elastomers have good elasticity, chemical corrosion resistance and excellent low-temperature performance, they can be widely used in many application scenarios.
[0003] At present, the production technology threshold of propylene-based elastomers is relatively high, resulting in very limited propylene-based elastomer products that can be actually used on the market. At present, there are very few companies that can produce PBE. Globally, only a few large chemical companies such as ExxonMobil, Dow Chemical and Mitsui Chemicals have the corresponding technical strength and resources to carry out large-scale production. Dow Chemical and Mitsui Chemicals With its first-mover advantage in technology and market, the company has taken a leading position in the limited propylene-based elastomer market. However, this highly concentrated production pattern has led to insufficient market competition, which in turn has resulted in a very limited variety of propylene-based elastomer products available on the market.
[0004] From the perspective of product performance, traditional propylene-based elastomers have significant defects: their melting point is relatively low, and this feature severely limits their application range in high-temperature environments. For example, in some industrial scenarios that need to withstand high temperatures, such as parts in the engine compartment of a car, sealing materials for high-temperature pipes, etc., traditional propylene-based elastomers may soften and deform due to increased temperature, and thus fail to meet actual use requirements. At the same time, low strength is also a major shortcoming of traditional propylene-based elastomers. When subjected to large external forces, such as in engineering structural components, buffer materials for heavy-duty transportation equipment, and other application scenarios, it is prone to cracking and damage, and cannot provide sufficient structural support and protection. These performance deficiencies have greatly narrowed the application areas of traditional propylene-based elastomers, so that they can only be used in limited areas with relatively low performance requirements.
[0005] In summary, propylene-based elastomers are currently facing the dual dilemma of single product due to production technology monopoly and limited application scope due to product performance limitations. New technological breakthroughs and innovations are urgently needed to improve this situation in order to meet the increasingly diversified and high-performance industrial needs. Summary of the invention
[0006] The purpose of the present invention is to provide a high melting point propylene-ethylene olefin polymer elastomer and a preparation method thereof, and to synthesize the propylene-ethylene olefin polymer elastomer with propylene and ethylene, thereby greatly improving the melting point, strength and elongation at break of traditional propylene-based elastomers.
[0007] To achieve the above objectives, the present technical solution provides a method for preparing a high melting point ethylene-propylene polymer elastomer, comprising the following steps: copolymerizing propylene and ethylene under the catalysis of a copolymerization catalyst under anhydrous and oxygen-free conditions, wherein the copolymerization catalyst is a single-active-center metallocene catalyst or a post-metallocene catalyst, and the molar ratio of propylene is greater than the molar ratio of ethylene.
[0008] In some embodiments, the molar ratio of propylene to ethylene is 200:1 to 1.01:1, preferably, the molar ratio of propylene to ethylene is 4:1, which helps to form a suitable propylene sequence and ethylene distribution in the molecular structure, thereby optimizing the physical and chemical properties of the polymer, such as melting point, strength and elasticity.
[0009] In some embodiments, the reaction temperature of the copolymerization reaction is 60-250°C. Preferably, the reaction temperature of the copolymerization reaction is 60°C. At this time, the reaction can proceed at a relatively ideal rate, which is conducive to the formation of a regular polymer chain structure and the reduction of side reactions, thereby improving the quality and performance stability of the polymer, so that the final elastomer has better thermoplasticity and mechanical properties.
[0010] In some embodiments, the polymerization pressure of the copolymerization reaction is 0.1-10Mpa, and preferably, the polymerization pressure of the copolymerization reaction is 0.7Mpa, which can provide a suitable intermolecular force environment for the reaction, promote the effective coordination and insertion reaction of propylene and ethylene monomers in the active center of the catalyst, and help to form a high-melting-point propylene-ethylene polymer elastomer with relatively uniform molecular weight distribution and stable performance, thereby ensuring the reliability and durability of the product in practical applications.
[0011] In some embodiments, propylene and ethylene are copolymerized under the catalysis of a copolymerization catalyst, and the copolymerization reaction is carried out in an intermittent, semi-continuous or continuous solution system, wherein the organic solvent in the copolymerization reaction system is a straight-chain alkane, isoalkane, cycloalkane or aromatic alkane having 4 to 10 carbon atoms. Preferably, the organic solvent is one or any combination of n-butane, n-pentane, isopentane, n-hexane, cyclohexane, n-heptane, isoheptane, n-octane, isooctane, n-decane, isoalkane oil, toluene, and xylene. These organic solvents can not only provide a good medium environment for the reaction, ensuring that the reactants are fully dissolved and evenly dispersed, but also because of their unique chemical structure and physical properties, they have a positive regulatory effect on the rate of the polymerization reaction, the molecular weight and distribution of the polymer, etc., which helps to improve the quality and performance of the product.
[0012] In some embodiments, the concentration of the copolymerization catalyst is 0.1 to 100 μmol / L, preferably 5 μmol / L, based on the volume of the organic solvent. This can effectively control the molecular weight and molecular structure of the polymer while ensuring the reaction efficiency, so that the resulting polymer elastomer has ideal mechanical properties and processing properties, which is convenient for subsequent molding and practical application.
[0013] The copolymerization catalyst of the present scheme can be selected from the metallocene catalyst of single active center or post-metallocene catalyst, selected from dimethylsilyl bis(2-methyl-4-phenylindenyl) zirconium dichloride, biscyclopentadienyl dimethyl hafnium, bisindenyl dimethyl zirconium, vinylidene bridged bisindenyl dichloride, dimethylsilyl bridged-bisindenyl dichloride, diphenyl carbon bridged-cyclopentadienyl-Hua-based zirconium dichloride, dimethylsilyl bridged-tetramethylcyclopentadienyl-tert-butylamino-dimethyltitanium, bisindenyl zirconium dichloride, bis[2-(3',5'-di-tert-butylphenyl)-indenyl] zirconium dichloride, bis(2-methyl-4,5-phenyl-indenyl) zirconium dichloride, biscyclopentadienyl-bisphenoxy zirconium, dimethylsilyl bridged bisindenyl dimethyl zirconium, diphenyl carbon bridged-cyclopentadienyl-Hua-based dimethyl zirconium, diphenyl carbon Bridged-cyclopentadienyl-(2-dimethylamino-Wu-yl) zirconium dichloride, dimethylsilyl-tetramethylcyclopentadienyl-tert-butylamino-titanium dichloride, dimethylsilyl-3-pyrrolylindenyl-tert-butylamino-dimethyltitanium, pentamethylcyclopentadienyl-(2-phenylphenoxy)-titanium dichloride, pentamethylcyclopentadienyl-(2,6-diisopropylphenoxy)-titanium dichloride, bis(3-methylsalicylidene-pentafluorophenylimino)titanium dichloride, bis(salicylidene-phenylimino)titanium dichloride, dimethylsilyl-3-pyrrolylindenyl-tert-butylamino-dimethyltitanium, [N-(3,5-di-tert-butylsalicylidene)-2-diphenylphosphinophenylimino] titanium trichloride, (2,3,4-trihydro-8-diphenylphosphino-quinolyl)tribenzylzirconium or any combination thereof.
[0014] The copolymerization mechanism of ethylene and propylene in the present scheme is as follows: the olefin is coordinated to the vacant active metal center of the copolymerization catalyst, and then the alkyl group of the growing chain migrates to the coordinated olefin, thereby inserting the transitional Mt-C alkyl bond. As this coordination-insertion process is repeated many times, the polymer chain grows or undergoes chain transfer. The resulting alkyl metal can coordinate and insert additional introduced monomers, which terminates the growth of the polymer chain and leads to the initiation of new polymer chains.
[0015] In some embodiments, propylene and ethylene are copolymerized under the co-catalysis of a copolymerization catalyst and a co-catalyst, wherein the molar ratio of the co-catalyst to the copolymerization catalyst is 1:1 to 10000:1.
[0016] The cocatalyst of this scheme is selected from one or any combination of methylaluminoxane, modified methylaluminoxane, tri(pentafluorophenyl)boron compound, tetra(pentafluorophenyl)boron compound, triisobutylaluminum, triethylaluminum, trimethylaluminum. The presence of the cocatalyst can significantly improve the activity and selectivity of the catalyst, and regulate the reaction rate and the molecular weight distribution of the polymer. The appropriate ratio of the cocatalyst to the copolymerization catalyst helps to optimize the catalytic performance of the reaction system, ensure that the reaction is carried out efficiently and stably, thereby obtaining a high melting point ethylene propylene polymer elastomer with ideal performance.
[0017] The anhydrous and oxygen-free conditions mentioned in this proposal refer to the fact that all materials are treated to remove water and oxygen.
[0018] In a specific embodiment, the present scheme carries out copolymerization of propylene and ethylene in a reactor. Specifically, the preparation method of the high melting point propylene ethylene polymer elastomer provided by the present scheme comprises:
[0019] The reactor and pipelines are cleaned at high temperature with triisobutylaluminum n-hexane solution to remove impurities such as water and oxygen in the system. Under nitrogen protection, the copolymerization catalyst solution, co-catalyst solution, propylene and ethylene are added to their respective storage tanks, and the temperature of the reactor and pipelines is heated. Turn on the metering pump and the gas booster pump, adjust the reactor agitator, adjust the flow of organic solvent, copolymerization catalyst, co-catalyst and ethylene to the set value, adjust the flow of propylene to half of the set value, and adjust the pressure in the reactor; after reaching an average residence time, adjust the flow of propylene to the set value. Collect the product at the discharge port with a container filled with acidified ethanol. The obtained product is washed with ethanol, filtered, and vacuum dried overnight under heating.
[0020] In this specific embodiment, the reaction time is 2 to 60 minutes, preferably, the reaction time is 15 minutes.
[0021] In this specific embodiment, the reaction kettle was cooled to 60° C., and then the organic solvent and the co-catalyst were added, and the stirring speed was set to 600 rpm for sufficient stirring.
[0022] In this specific embodiment, the pressure of the reactor was increased to 0.7 MPa.
[0023] In this specific embodiment, the high melting point ethylene propylene polymer elastomer is obtained by vacuum drying at 70° C. for more than 8 hours.
[0024] In the second aspect, the present scheme provides a high melting point propylene olefin polymer elastomer, which is synthesized using the above-mentioned preparation method of the high melting point propylene olefin polymer elastomer, and is a copolymer of ethylene and propylene, wherein ethylene accounts for 10% to 49.9%, ethylene and propylene are randomly arranged, and ethylene is randomly inserted into the polypropylene sequence.
[0025] The structure of the high melting point propylene ethylene polymer elastomer synthesized in this scheme is shown in the following formula (I):
[0026]
[0027] Wherein a represents the amount of ethylene in the comonomer, b represents the amount of propylene in the comonomer, and w represents the amount of the comonomer.
[0028] The high melting point propylene ethylene polymer elastomer synthesized in this scheme has a melting point of 50-200° C., elastic recovery rate, and fracture.
[0029] Compared with the prior art, this technical solution has the following characteristics and beneficial effects:
[0030] This scheme uses propylene and ethylene as raw materials to copolymerize under the action of a copolymerization catalyst to synthesize a high-melting-point propylene-ethylene olefin polymer elastomer. Compared with traditional propylene-based polymers, the high-melting-point propylene-ethylene olefin polymer elastomer has similar or even higher melting point, strength and elongation at break. Since the polymer contains atactic propylene and isotactic propylene sequences, it exhibits higher zero-shear viscosity and melt index, and the shear thinning phenomenon is obvious during processing, which is conducive to processing and molding. At the same time, in the blending process of polyethylene and polypropylene, it shows a significant volume expansion effect, effectively eliminates the phase interface, and shows lower cost and wider application than POE. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a melting point test data chart of the high melting point propylene ethylene polymer elastomer synthesized in Example 1 of this scheme.
[0032] Figure 2 This is the melting point test data chart of industrial sample Dow 2300.
[0033] Figure 3 This is the carbon nuclear magnetic resonance spectrum of the high melting point propylene ethylene polymer elastomer synthesized in Example 1 of this scheme.
[0034] Figure 4 This is a comparison of the spectra of the high melting point propylene ethylene polymer elastomer synthesized in Example 1 with those of industrial samples. DETAILED DESCRIPTION
[0035] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0036] Those skilled in the art should understand that, in the disclosure of the present invention, the orientation or position relationship indicated by the terms "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc. are based on the orientation or position relationship shown in the drawings, which are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the above terms should not be understood as limiting the present invention.
[0037] Example 1-1 Synthesis of high melting point propylene ethylene polymer elastomer:
[0038] In this experiment, the copolymerization catalyst used was rac-dimethylsilyl bridged-bis(2-methyl-4-phenyl-indenyl) zirconium dichloride, the cocatalyst used was modified methylaluminoxane, the solvent was n-hexane, and the monomers were ethylene and propylene. The polymerization experiment was carried out in a continuous solution system. The reactor and pipeline were cleaned at high temperature with triisobutylaluminum n-hexane solution to remove impurities such as water and oxygen in the system. Under nitrogen protection, the copolymerization catalyst solution, cocatalyst solution, propylene and ethylene were added to their respective storage tanks. The temperature of the reactor and pipeline was heated. The metering pump and the gas booster pump were turned on, the reactor agitator was adjusted, and the flow rates of the solvent, copolymerization catalyst, cocatalyst and ethylene were adjusted to the set value, wherein the feed molar ratio of propylene to ethylene in the ethylene-propylene mixed gas was 8:2; the flow rate of propylene was adjusted to half of the set value, and the pressure in the reactor was regulated to 0.7MPa; after reaching an average residence time, the flow rate of propylene was adjusted to the set value. The product was collected at the discharge port using a container filled with acidified ethanol. The obtained product was washed with ethanol, filtered, and dried in vacuum under heating overnight.
[0039] The concentration of the copolymerization catalyst co-actuator was 5 μmol / L, the concentration of the co-catalyst was 5 mmol / L, the molar ratio of the co-catalyst to the copolymerization catalyst was 1000, the feed molar ratio of propylene to ethylene was 8:2, and all the materials used in the experiment were treated with dehydration and deoxygenation.
[0040] The molecular weight (Mw and Mn) and its distribution index (PDI) of the polymer were determined by high temperature gel permeation chromatography (PL-GPC220) using 1,2,4-trichlorobenzene as solvent, a 0.1-0.3 wt% polymer solution was prepared at 150°C, and a narrow molecular weight distribution polystyrene was used as a standard sample at 150°C, with a solvent flow rate of 1.0 ml / min. The parameter K = 17.5 × 10 -4 , α=0.67, PP parameter K=19.0×10 -4 , α=0.725.
[0041] The melting point (Tm) of the copolymer was determined by TA Instruments Q200. 5.0-7.0 mg of the polymer sample was heated to 200°C at 30°C / min, kept constant for 5 minutes to eliminate the thermal history, then cooled to -90°C at 10°C / min, kept constant for 3 minutes, and then heated to 200°C at 10°C / min. The melting point of the polymer was obtained from the second heating curve.
[0042] The average composition of the comonomers in the copolymers was determined by carbon NMR spectroscopy ( 13 C NMR) was measured at 125°C, with the instrument model being Bruker AC 400. The polymer was prepared into a 10% deuterated o-dichlorobenzene solution at 150°C and pre-dissolved for 3 to 4 hours to make the sample solution uniform. The instrument parameters were optimized as follows: pulse angle 90°, reverse proton decoupling, pulse delay time 8s, collection time 1.3s, and spectrum width 8000Hz, with an average scan number of no less than 5000 times.
[0043] Example 1-2
[0044] The experimental conditions are as follows: after the system reaches a steady state, the reaction temperature in the kettle is 70°C, the concentration of the copolymerization catalyst is 0.5 μmol / L, the concentration of the co-catalyst is 5 mmol / L, the molar ratio of the co-catalyst to the copolymerization catalyst is 10000, and the other experimental conditions are the same as those in Example 1-1.
[0045] Examples 1-3
[0046] The experimental conditions are as follows: after the system reaches steady state, the reaction temperature in the kettle is 240°C, the concentration of the copolymerization catalyst is 95 μmol / L, the concentration of the co-catalyst is 47.5 mmol / L, the molar ratio of the co-catalyst to the copolymerization catalyst is 50, and the other experimental conditions are the same as those in Example 1-1.
[0047] Examples 1-4
[0048] The experimental conditions are as follows: after the system reaches a steady state, the concentration of the copolymerization catalyst in the kettle is 0.5 μmol / L, the concentration of the co-catalyst is 5 mmol / L, the molar ratio of the co-catalyst to the main catalyst is 10000, and the other experimental conditions are the same as those in Example 1-1.
[0049] Examples 1-5
[0050] The experimental conditions are as follows: after the system reaches a steady state, the concentration of the copolymerization catalyst in the kettle is 95 μmol / L, the concentration of the co-catalyst is 47.5 mmol / L, the molar ratio of the co-catalyst to the main catalyst is 50, and the other experimental conditions are the same as those in Example 1-1.
[0051] Examples 1-6
[0052] The experimental conditions are as follows: after the system reaches a steady state, the molar ratio of ethylene to propylene in the kettle is 5:2, the operating pressure is 10 MPa, and the other experimental conditions are the same as those in Example 1-1.
[0053] Examples 1-7
[0054] The experimental conditions are as follows: after the system reaches a steady state, the molar ratio of ethylene to propylene in the kettle is 1:1.01, the operating pressure is 0.1 MPa, and the other experimental conditions are the same as those in Example 1-1.
[0055] Examples 1-8
[0056] The experimental conditions are as follows: the copolymerization catalyst is changed to bis-indenyl dimethyl zirconium, and the kettle residence time is 2 minutes. Other experimental conditions are the same as those in Example 1-1.
[0057] Examples 1-9
[0058] The experimental conditions are as follows: the copolymerization catalyst is changed to dimethylsilyl-bridged bis-indenyl dimethyl zirconium, and the kettle residence time is 60 minutes. Other experimental conditions are the same as those in Example 1-1.
[0059] Examples 1-10
[0060] The experimental conditions are: changing the ethylene-propylene feed ratio to 1:200, changing the solvent to toluene, and the other experimental conditions are the same as those in Example 1-1.
[0061] Test data:
[0062] The molecular weight (Mw and Mn) and its distribution index (PDI) of the polymer were determined by high temperature gel permeation chromatography (PL-GPC220). 1,2,4-trichlorobenzene was used as solvent to prepare a 0.1-0.3 wt% polymer solution at 150°C, and polystyrene with narrow molecular weight distribution was used as standard sample at 150°C. The solvent flow rate was 1.0 ml / min. The parameter K = 17.5 × 10 -4 , α=0.67, PP parameter K=19.0×10 -4 , α=0.725, and the polymer molecular weight data Mw of the high melting point propylene olefin polymer elastomer synthesized in Example 1 is tested to be 245 kDa.
[0063] The melting point (Tm) of the copolymer was measured by TA Instruments Q200. 5.0-7.0 mg of the polymer sample was heated to 200°C at 30°C / min, kept at this temperature for 5 minutes to eliminate the thermal history, then cooled to -90°C at 10°C / min, kept at this temperature for 3 minutes, and then heated to 200°C at a rate of 10°C / min. The melting point of the polymer was obtained from the second heating curve. The melting point test data of the high melting point propylene olefin polymer elastomer synthesized in Example 1 were obtained by testing. Figure 1 As shown in the figure, the melting point test data of industrial sample Dow 2300 is as follows Figure 2 As shown, it can be seen that the melting point of the high melting point propylene ethylene polymer elastomer synthesized in Example 1 is significantly improved.
[0064] The average composition of the comonomers in the copolymers was determined by carbon NMR spectroscopy ( 13 C NMR) was measured at 125°C, and the instrument model was Bruker AC 400. The polymer was prepared into a 10% deuterated o-dichlorobenzene solution at 150°C, and was pre-dissolved for 3 to 4 hours to make the sample solution uniform. The instrument parameters were optimized as follows: pulse angle 90°, reverse proton decoupling, pulse delay time 8s, collection time 1.3s and spectrum width 8000Hz, and the average scanning number was not less than 5000 times. The nuclear magnetic resonance carbon spectrum of the high melting point propylene ethylene polymer elastomer synthesized in Example 1 was obtained by testing as follows: Figure 3 As shown, the spectrum of the high melting point propylene ethylene polymer elastomer synthesized in Example 1 is compared with the spectrum of the industrial sample. Figure 4 As shown, the industrial sample refers to the industrial sample Dow 2300.
[0065] The performance test data table of the products of Examples 1-1 to 1-10 and Versify 3300 is shown in Table 1: Table 1 Performance test data table of the products of Examples 1-1 to 1-10 and Versify 3300
[0066]
[0068] It is to be understood that the term "one" should be understood as "at least one" or "one or more", that is, in one embodiment, the number of an element may be one, while in another embodiment, the number of the element may be multiple, and the term "one" should not be understood as a limitation on the quantity.
[0069] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that are the same or similar to those of the present application fall within the protection scope of the present invention.
Claims
1. A method for preparing a high melting point propylene ethylene polymer elastomer, characterized in that: The following steps are involved: Propylene and ethylene are copolymerized under the catalysis of a copolymerization catalyst under anhydrous and oxygen-free conditions, wherein the copolymerization catalyst is a metallocene catalyst or a post-metallocene catalyst with a single active center, and the molar ratio of propylene is greater than the molar ratio of ethylene.
2. The method for preparing a high melting point propylene ethylene polymer elastomer according to claim 1, characterized in that: The molar ratio of propylene to ethylene is 200:1 to 1.01:
1.
3. The method for preparing a high melting point propylene ethylene polymer elastomer according to claim 2, characterized in that: The molar ratio of propylene to ethylene is 4:
1.
4. The method for preparing a high melting point propylene ethylene polymer elastomer according to claim 1, characterized in that: The reaction temperature of the copolymerization reaction is 60-250° C., and the polymerization pressure of the copolymerization reaction is 0.1-10 MPa.
5. The method for preparing a high melting point propylene ethylene polymer elastomer according to claim 1, characterized in that: Propylene and ethylene are copolymerized under the catalysis of a copolymerization catalyst. The copolymerization reaction is carried out in an intermittent, semi-continuous or continuous solution system, wherein the organic solvent in the copolymerization reaction system is a straight-chain alkane, isoalkane, cycloalkane or aromatic alkane having 4 to 10 carbon atoms.
6. The method for preparing a high melting point propylene ethylene polymer elastomer according to claim 5, characterized in that: The concentration of the copolymerization catalyst is 0.1 to 100 μmol / L based on the volume of the organic solvent.
7. The method for preparing a high melting point propylene ethylene polymer elastomer according to claim 1, characterized in that: The copolymerization catalyst is selected from dimethylsilyl bis(2-methyl-4-phenylindenyl) zirconium dichloride, biscyclopentadienyl dimethyl hafnium, bisindenyl dimethyl zirconium, vinylidene bridged bisindenyl dichloride, dimethylsilyl bridged-bisindenyl dichloride, diphenyl carbon bridged-cyclopentadienyl-Wu-based zirconium dichloride, dimethylsilyl bridged-tetramethylcyclopentadienyl-tert-butylamino-dimethyltitanium, bisindenyl zirconium dichloride, bis[2-(3',5'-di-tert-butylphenyl)-indenyl] zirconium dichloride, bis(2-methyl-4,5-phenyl-indenyl) zirconium dichloride, biscyclopentadienyl-bisphenoxy zirconium, dimethylsilyl bridged bisindenyl dimethyl zirconium, diphenyl carbon bridged-cyclopentadienyl-Wu-based dimethyl zirconium, dimethylsilyl bridged Phenyl carbon bridged-cyclopentadienyl-(2-dimethylamino-Wu-yl) zirconium dichloride, dimethylsilyl bridged-tetramethylcyclopentadienyl-tert-butylamino-titanium dichloride, dimethylsilyl bridged-3-pyrrolylindenyl-tert-butylamino-dimethyltitanium, pentamethylcyclopentadienyl-(2-phenylphenoxy)-titanium dichloride, pentamethylcyclopentadienyl-(2,6-diisopropylphenoxy)-titanium dichloride, bis(3-methylsalicylidene-pentafluorophenylimino) titanium dichloride, bis(salicylidene-phenylimino) titanium dichloride, dimethylsilyl bridged-3-pyrrolylindenyl-tert-butylamino-dimethyltitanium, [N-(3,5-di-tert-butylsalicylidene)-2-diphenylphosphinophenylimino] titanium trichloride, One or any combination of (2,3,4-trihydro-8-diphenylphosphino-quinolyl)tribenzylzirconium.
8. The method for preparing a high melting point propylene ethylene polymer elastomer according to claim 1, characterized in that: Propylene and ethylene are copolymerized under the co-catalysis of a copolymerization catalyst and a co-catalyst, wherein the molar ratio of the co-catalyst to the copolymerization catalyst is 1:1 to 10000:1, and the co-catalyst is selected from one or any combination of methylaluminoxane, modified methylaluminoxane, tri(pentafluorophenyl)boron compound, tetra(pentafluorophenyl)boron compound, triisobutylaluminum, triethylaluminum, and trimethylaluminum.
9. A high melting point propylene ethylene polymer elastomer, characterized in that: The high melting point propylene ethylene polymer elastomer is prepared according to the preparation method of any one of claims 1 to 8, and its melting point is not less than 100°C.
10. A high melting point propylene ethylene polymer elastomer, characterized in that: The high melting point ethylene-propylene olefin polymer elastomer prepared by the preparation method according to any one of claims 1 to 9 is a copolymer of ethylene and propylene, wherein ethylene accounts for 10% to 49.9%, and ethylene and propylene are randomly arranged.
Citation Information
Patent Citations
Propylene polymer
JP2001288221A
Propylene ethylene polymers
US20020004575A1
Propylene ethylene polymers and production process
US20040236042A1
Propylene ethylene polymers and production process
US20070244276A1
Propylene ethylene copolymers
WO2002083753A1